Amulet : the last council / 4 - Kibuishi, Kazu, 1978- (Amulet, 2011)
Upon arriving in Cielis, Emily and her friends find the once busy streets deserted and the remaining townspeople living in fear, and after Emily is escorted to the Academy to compete for a spot on the Guardian Council, the most powerful Stonekeepers, an awful secret is gradually uncovered.